Caminhos da reforma tributária no Brasil: 1980-2009 - Adriano Miglio Porto (2009)
This paper analyzes the evolution of tax reform since the great crisis of Brazilian State funding in the 1980´s until 2009. It emphasizes the importance of a comprehensive and interdisciplinary approach including Sociology, Economics and Political Science, especially for greater theoretical understanding of this process. The inter-systemicexternal environment (globalization, financialization), macroeconomic policy, ideology and internal political dynamics (conflict, actors and institutional framework) helps to visualize the context that led to changes in tax policy in these three decades. The concept of social-tax contract, supported by broad coalition of political forces, helps to understand the legitimacy of the tax system. The changes are directly related to politicalconflicts and the government view on the role of the state and its priorities for the development of Brazil. The system of institutional vetoes and maintenance of monetary stability with investments in the construction of Well-Being in Brazil guide the tax trajectory of Brazil. But there are strong questions about the tax system as a regressive tax funding progressive social policies and the need for greater efficiency to encourageproduction and employment. The tax legitimacy tends to increase when the expenses of the state have lower expression in the financial and advance in social purposes.